Clinical and Social Findings of Childhood Epilepsy - H Wali , Marwa; SH Jebr , Mehdi; SH Mahmood , Najdat (Diyala Journal of Medicine, 2021)
Background: Seizures are defined as a transient occurrence of signs and symptoms due to the abnormal, excessive, or synchronous neuronal activity in the brain characterized by abrupt and involuntary skeletal muscle activity. Seizure is related to specific risk factors like positive family history, fever, infections, neurological comorbidity, premature birth, mother’s alcohol abuse, and smoking in pregnancy. Epilepsy is the most frequent chronic neurologic condition in children. Studies have suggested declining incidence rates of childhood epilepsy in high-income countries during the last decades. Objective: To describe the clinical features and social findings of epilepsy in children, and to evaluate some risk factors associated with control of epilepsy. Patients and Methods: This cross-sectional study was conducted in the pediatric department of Albatool teaching hospital in Diyala province, Iraq. A total of 100 children were included in the study from February 2020 to May 2020. All children diagnosed with epilepsy in this study. Results: One hundred children with epilepsy, their mean age was 5.96± 3.33 years (range 1-14 years). Of the 48(48%) children were male and 52(52%). Of the total patients, 79% were free from seizure on AED, 21% of them were refractory to treatment.Patients without developmental delay (88.7%, p=0.012) can be controlled by AED. Patients who had idiopathic seizures (87.5%, p=0.04) can be controlled by AED. Patients who had seizure attacks can be controlled by AED more than patients who had weekly or monthly seizure attacks (97.4%) (p<0.001). Patients who had been treated by monotherapy (94.7%, p=0.012) can be controlled more than patients who were treated by multidrug therapy. Affected social interaction and need more supervision were factors that detected more in patients with refractory epilepsy, p=0.04, 0.01 respectively. While there was no association between frightened other people and epilepsy control. Conclusion: Most of the patients are characterized by: treatment approach monotherapy, less affected by social interaction and need less supervision. Patients with refractory epilepsy had opposite factors.